Quels outils d’aide à la réussite pour quels profils d’apprenants dans un MOOC hybride ? - Karim Boumazguida; Gaëtan Temperman; Bruno De Lièvre (Recherches en Éducation, 2022)
In this contribution, we focus on the performance of the enrollees in a hybrid MOOC developed in French-speaking Belgium. We analyse the learning traces of the learners collected in the MOOC. We evaluate their progress between a pre-test and a post-test and analyse the different variables (viewing videos, exchanges on communication tools, participation in quizzes, etc.) linked to the learning process that may influence it. Although the learners made overall progress, our results did not allow us to identify specific factors explaining their level of mastery. Finally, we identified three learner profiles according to their autonomous use of the resources proposed in the hybrid MOOC and their performance: the "non-engaged", the "moderately engaged" and the "not very engaged communicators".